Sources of food price volatility and child malnutrition in Niger and Malawi. (April 2016) - Cornia, Giovanni Andrea; Deotti, Laura; Sassi, Maria
Highlights: Domestic food prices as a determinant of child malnutrition in Malawi and Niger. Impact of food price seasonality on child malnutrition. Child malnutrition rises during famines. Long term impact of agricultural policies on child malnutrition. Abstract: In recent times, considerable attention has been paid to the nutritional impact of the sharp hikes in the international food prices which took place in 2007–8 and 2010–11. While understandable, this growing focus has perhaps obscured the impact of other variables affecting malnutrition in Sub-Saharan Africa, i.e. the long-term impact of agricultural policies on food supply and prices, large and persistent seasonal variations in food prices, and the impact of famines which still affect parts of the continent. This paper focuses on the relative impact of these factors on child malnutrition (measured by the number of child admissions to feeding centres) in Malawi and Niger, two countries which closely represent the situation of other small, landlocked, subsistence agricultural economies facing severe food security problems. Our analysis shows that in these countries the drivers of changes in domestic staple prices and child malnutrition are related not only – or not primarily – to variations of international food prices but also to the impact of agricultural policies on food production and prices, in a persistent food price seasonality, and in recurrent and poorly managed famines. These factors can exert a strong upward pressure on food prices and child malnutrition even during years of falling international prices.